The latin American psychiatrist: Profile and degree of satisfaction with the specialty (2009)
Objectives. The primary objective is to describe the profile of the psychiatric members of a national psychiatry association in 19 Latin American countries (Argentina, Bolivia, Brazil, Colombia, Costa Rica, Cuba, Dominican Republic, Ecuador, Chile, El Salvador, Guatemala, Honduras, Mexico, Nicaragua, Peru, Panama, Paraguay, Uruguay, and Venezuela). Secondary objectives are to evaluate job satisfaction and examine the factors related with job satisfaction. Methods and materials. A total of 8,028 psychiatrists, members of a national psychiatry association in Latin America, were identified. A probabilistic stratified sample of 2465 psychiatrists was designed and they were asked to fill out an anonymous electronic survey. Results. A sample of 1,292 Latin American psychiatrists was obtained between April 2005 and July 2006 (52.4% of the designed sample). Response rates were superior to 70% in 11 countries. Mean age was 48.2 years, mean experience was 18.2 years; 63.8% were male and 99.9% of the surveyed psychiatrists were working as psychiatrists. Most of the respondents declared being satisfied with their quality of life (70.8%), a slightly larger percentage reported they were satisfied with their work (86.4%). However, 35.3% of the psychiatrists reported being unsatisfied with the income perceived for their economic activity as psychiatrists. Factors associated with job dissatisfaction are described. Conclusions. In Latin America, there is lower satisfaction with the incomes obtained from psychiatric practice and with the quality of life level. Nonetheless, the level of commitment with the profession in itself and job satisfaction remain similar to those reported in developed countries.